2014
DOI: 10.5826/dpc.0402a04
|View full text |Cite
|
Sign up to set email alerts
|

Papillary adenocarcinoma in situ of the skin: report of four cases

Abstract: Although rare isolated cases of adenocarcinoma in situ of skin have been reported in the literature, adenocarcinoma in situ of skin as a concept and as a diagnostic category has not been established in the field of dermatopathology. In this work, four cases of papillary adenocarcinoma in situ of the skin are presented. In addition, the notion that lesions previously reported in the medical literature under the term of “papillary eccrine adenoma” are actually adenocarcinoma in situ is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…Asgari have had a different view and thought that the so-called PEA is actually cutaneous papillary AIS. 3 In the case report by Wu et al, a focus of invasive adenocarcinoma with lack of the outer myoepithelial layer was identified and this finding further supports the notion that so-called PEA is really AIS. Admittedly cutaneous AIS has not been recognized by many as a diagnostic entity yet, thus many examples of cutaneous AIS have been misinterpreted as either benign neoplasm or invasive carcinoma in the literature.…”
Section: While Chen Andmentioning
confidence: 57%
See 1 more Smart Citation
“…Asgari have had a different view and thought that the so-called PEA is actually cutaneous papillary AIS. 3 In the case report by Wu et al, a focus of invasive adenocarcinoma with lack of the outer myoepithelial layer was identified and this finding further supports the notion that so-called PEA is really AIS. Admittedly cutaneous AIS has not been recognized by many as a diagnostic entity yet, thus many examples of cutaneous AIS have been misinterpreted as either benign neoplasm or invasive carcinoma in the literature.…”
Section: While Chen Andmentioning
confidence: 57%
“…Admittedly cutaneous AIS has not been recognized by many as a diagnostic entity yet, thus many examples of cutaneous AIS have been misinterpreted as either benign neoplasm or invasive carcinoma in the literature. 3,6,7 We believe the case described by Wu et al represents such an example here.…”
Section: While Chen Andmentioning
confidence: 69%
“…Obviously not. In their paper on 4 cases of what they consider AIS, Chen and Asgari recommend “simple complete but conservative excision,” which is essentially what happened to the patient we reported. So, regardless of the name such lesions are given, the end result is the same: complete excision.…”
mentioning
confidence: 65%
“…There is, however, a disadvantage to calling too many entities AIS. Chen and Asgari suggest that papillary eccrine adenomas (PEA) are AIS . They present no definitive biologic or follow‐up evidence to support this claim.…”
mentioning
confidence: 99%
“…13 These derive from structures of common origin, such as apocrine and eccrine sweat glands, sebaceous glands, and hair follicles, which also may appear on the digits as well as trunk and extremities. [14][15][16][33][34] The identification is initially quite challenging, and reliance on IHC for differentiation is paramount to categorizing those as adnexal. 16 Review has suggested mean age of 63 years, more common in men than women by 2:1 ratio, and has even described an estrogen receptor-positive tumor in a male.…”
Section: Discussion and Medical Oncology Considerationmentioning
confidence: 99%